Student-Related Variables as Predictors of Attitude to and Achievement in Literature-In-English in Southwestern Nigeria (2014)
The West African Examinations Council results between 2007 and 2013 revealed that students’ performance in Literature-in-English was poor despite various innovative instructional strategies employed in the teaching of the subject. Efforts which aimed at improving students’ attitude to and achievement in the subject had focused more on teacher-related than student-related variables. This study therefore investigated the extent to which student-related variables (English Language proficiency, locus of control, study habit, text utilisation and class participation) predict students’ attitude to and achievement in Literature-in-English in Southwestern Nigeria. The study adopted the survey research design. Stratified and simple random sampling techniques were adopted in selecting 1,486 SS II, Literature-in-English students from 10 randomly selected public secondary schools each from Ekiti (504), Osun (533) and Ogun (449) States. Literature-in-English Achievement Test (r=0.76), Attitude to Literature-in-English Questionnaire (r=0.74), English Language Proficiency Test (r=0.74), Locus of Control Scale (r=0.78), Study Habit Questionnaire (r=0.78), Text Utilisation Questionnaire (r=0.82) and Class Participation Observation Scale (r=0.79) were used for data collection. Four research questions were answered. Data were analysed using Pearson’s product-moment correlation and multiple regression at 0.05 level of significance. The composite contribution of all the independent variables was significant to achievement (F5,1480 = 45.84) and attitude (F5,1480 = 110.61). English Language Proficiency (β=.45), study habit (β = .15), text utilisation (β = .14) and locus of control (β=.18) made significant relative contributions to attitude, but class participation did not. English Language proficiency (β =.14), locus of control (β=.14), text utilisation (β=.10), and class participation (β=.16) had significant relative contributions to achievement but study habit did not. These variables accounted for 13.4% of the variation in achievement and 27.2% in attitude. English Language proficiency (r =.14), locus of control (r =.25), study habit (r =.31), text utilisation (r =-.21), class participation (r = .31) had significant positive relationship with achievement in Literature-in-English. English Language proficiency (r=.47) and text utilisation (r=.23) had significant positive relationships with attitude but locus of control, study habit and class participation did not. There was no significant effect of the variables in the three states on attitude to and achievement of students in Literature-in-English. Student-related variables predicted attitude to and achievement in Literature-in-English in the states. Hence, teachers are expected to take cognizance of these student-related variables in order to improve students’ attitude to and achievement in Literature-in-English